Sigma-2 Receptor/TMEM97 and PGRMC-1 Increase the Rate of Internalization of LDL by LDL Receptor through the Formation of a Ternary Complex. Issue 1 (December 2018) - Riad, Aladdin; Zeng, Chenbo; Weng, Chi-Chang; Winters, Harrison; Xu, Kuiying; Makvandi, Mehran; Metz, Tyler; Carlin, Sean; Mach, Robert
Abstract CRISPR/Cas gene studies were conducted in HeLa cells where either PGRMC1, TMEM97 or both proteins were removed via gene editing. A series of radioligand binding studies, confocal microscopy studies, and internalization of radiolabeled or fluorescently tagged LDL particles were then conducted in these cells. The results indicate that PGRMC1 knockout (KO) did not reduce the density of binding sites for the sigma-2 receptor (σ2R) radioligands, [125 I]RHM-4 or [3 H]DTG, but a reduction in the receptor affinity of both radioligands was observed. TMEM97 KO resulted in a complete loss of binding of [125 I]RHM-4 and a significant reduction in binding of [3 H]DTG. TMEM97 KO and PGRMC1 KO resulted in an equal reduction in the rate of uptake of fluorescently-tagged or3 H-labeled LDL, and knocking out both proteins did not result in a further rate of reduction of LDL uptake. Confocal microscopy and Proximity Ligation Assay studies indicated a clear co-localization of LDLR, PGRMC1 and TMEM97. These data indicate that the formation of a ternary complex of LDLR-PGRMC1-TMEM97 is necessary for the rapid internalization of LDL by LDLR.